2007
DOI: 10.1021/bi7000032
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions Differentially Influence the Aggregation and Deposition of Alzheimer's β-Amyloid on a Solid Template

Abstract: The abnormal deposition and aggregation of beta-amyloid (Abeta) on brain tissues are considered to be one of the characteristic neuropathological features of Alzheimer's disease (AD). Environmental conditions such as metal ions, pH, and cell membranes are associated with Abeta deposition and plaque formation. According to the amyloid cascade hypothesis of AD, the deposition of Abeta42 oligomers as diffuse plaques in vivo is an important earliest event, leading to the formation of fibrillar amyloid plaques by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(178 citation statements)
references
References 28 publications
10
163
0
Order By: Relevance
“…Based on TEM images, under these conditions, the morphology of the fibers generated appears quite similar for fibers formed with and without the presence of Cu 2ϩ ions. We note that previous studies by other groups using TEM did not reveal fibers in the presence of Cu 2ϩ because the high A␤ and Cu 2ϩ concentrations used caused amorphous precipitation (42)(43)(44)(45)(46). Furthermore, the Cu 2ϩ -generated fibers are capable of seeding fiber formation of fresh, metal-free A␤ as indicated by a reduction in the lag time (see supplemental Fig.…”
Section: Coppermentioning
confidence: 70%
See 1 more Smart Citation
“…Based on TEM images, under these conditions, the morphology of the fibers generated appears quite similar for fibers formed with and without the presence of Cu 2ϩ ions. We note that previous studies by other groups using TEM did not reveal fibers in the presence of Cu 2ϩ because the high A␤ and Cu 2ϩ concentrations used caused amorphous precipitation (42)(43)(44)(45)(46). Furthermore, the Cu 2ϩ -generated fibers are capable of seeding fiber formation of fresh, metal-free A␤ as indicated by a reduction in the lag time (see supplemental Fig.…”
Section: Coppermentioning
confidence: 70%
“…These initial studies did not make the distinction between amorphous aggregates, which are nontoxic to cells, and the formation of amyloid fibers. Further investigations using the fiber specific fluorophore thioflavin T (ThT) suggested that Zn 2ϩ and Cu 2ϩ only promote amorphous aggregation of A␤ and actually inhibit fiber formation and cell toxicity (42)(43)(44)(45)(46). We became interested in the factors that promote self-association of A␤, the relationship between amorphous aggregation and amyloid fiber formation, and a role for Cu 2ϩ ions in promoting fiber formation.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…The mechanism by which A␤ aggregates is not fully understood, although it has been shown that peptide concentration, ions, pH, and temperature influence the A␤ oligomerization process and fibril conversion (Isaacs et al, 2006;Ha et al, 2007). In the present study, we generated two conditioned media (RPMI and Neurobasal) containing 10 M analogs of soluble A␤Os, A␤Fs, or amorphous A␤As.…”
Section: A␤o A␤f and A␤a Conditioned Media Generation And Toxicitymentioning
confidence: 98%
“…24) Briefly, the core promoter sequence of human ho-1 (-56 to -206) was cloned from the human genome and inserted into pGL3-Basic vector (Promega). Further, the AB1 enhancer-like sequence of human ho-1 was amplified using the primer Fw-Ab1: 5-GCTAGCTAATCCTTTCCCGAGCCA-3, Rv-Ab1: 5-GCTGGATATCTGAGGAAAAC-3.…”
Section: )mentioning
confidence: 99%